The Effect of Project-Based Learning Implementation on Senior High School Students’ 4C Capability - Faizah, Cut; Zuhra, Cut Mulia (English LAnguage Study and TEaching, 2024)
This experimental This qualitative study investigates the effect of Project-Based Learning (PjBL) implementation on students' capacities in sharpening 21st century soft skill, commonly called the 4Cs. The 4Cs include communication, collaboration, creativity and critical thinking. The study was conducted at SMA Labschool Unsyiah and the sample of the study were class X IPS in the academic year of 2021/2022. The total number of students in this class was 30 consisting of 13 males and 17 females. The data were collected through an observation when the English teacher was teaching descriptive text using PjBL. An observation sheet consisting 4Cs items which were broken down into 15 sub descriptions was used. The data were then analyzed using simple percentage formula to get the final grade. The results revealed that PjBL pedagogy brings positive effects on students' 4Cs capacities.